Spontaneous mode locking of a multimode semiconductor laser under continuous wave operation - Chomet, Baptiste; Blin, Stéphane; Beaudoin, Grégoire; Pantzas, Konstantinos; Sagnes, Isabelle; Denet, Stéphane; Garnache, Arnaud (Frontiers in Photonics, 2023)
Self-starting mode-locking is observed in a laser based on a compact III-V diode-pumped quantum-well surface-emitting semiconductor laser technology with a saturable-absorber-free but dispersive cavity. Continuous wave generation of picosecond pulses at a rate of 100 GHz is demonstrated by recording microwave intensity noises, beat frequency, time-resolved optical spectra, and intensity autocorrelation. Coherence of the pulse train is obtained through the frequency noise measurement of the demodulated beat note, demonstrating a timing jitter as low as 110 fs, near the quantum limit. Using a theoretical model based on a generalized Haus master equation, we demonstrate the existence of this mode locked state without the need for saturable absorption. The fundamental physical mechanism is the interplay between self-phase modulation and anomalous dispersion like in cavity soliton together with light–matter interaction-induced time symmetry breaking.